Respons mahasiswa terhadap buku panduan dan kegiatan pelatihan “teknik monitoring kura-kura cyclemys oldhamii” - Annisa Puji Astuti; Aceng Ruyani; Wiryono Wiryono (PendIPA Journal of Science Education, 2017)
This study aimed to know the students’s response to the guidebooks and training activities entitled "Monitoring Technique of the Cyclemys oldhamii Tortoise " in the ex situ conservation area Taman Pintar University of Bengkulu. The results showed that students responded positively to the guidebooks and training activities. Forestry students was very interested in the field practices related to the technique and monitoring activities of the C.oldhamii tortoise, while MIPA students was interested  in knowledge of the habitat, morphology, and its conservation. Forestry students showed the biggest  response to conserve  C.oldhamii and other tortoises, meanwhile MIPA students was more interested to do the next  observations and research about C.oldhamii and other tortoises for thesis research. Forestry and MIPA students could explain the benefits and plans after the training activities "Technique Monitoring of the Cyclemys oldhamii Tortoise" well.